2010
DOI: 10.1186/1471-2121-11-25
|View full text |Cite
|
Sign up to set email alerts
|

Functional neural differentiation of human adipose tissue-derived stem cells using bFGF and forskolin

Abstract: BackgroundAdult mesenchymal stem cells (MSCs) derived from adipose tissue have the capacity to differentiate into mesenchymal as well as endodermal and ectodermal cell lineage in vitro. We characterized the multipotent ability of human adipose tissue-derived stem cells (hADSCs) as MSCs and investigated the neural differentiation potential of these cells.ResultsHuman ADSCs from earlobe fat maintained self-renewing capacity and differentiated into adipocytes, osteoblasts, or chondrocytes under specific culture c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
197
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(215 citation statements)
references
References 70 publications
16
197
1
1
Order By: Relevance
“…Neurofilaments are intermediate filaments found in neurons and they are believed to function primarily to provide structural support for axons. 29 In our study, the expression levels of NF-L, NF-H, and TuJ1 were significantly increased in npMSCs that had differentiated into neurogenic cells. This result suggests that npMSCs have the potential to differentiate into neuronlike cells.…”
supporting
confidence: 47%
“…Neurofilaments are intermediate filaments found in neurons and they are believed to function primarily to provide structural support for axons. 29 In our study, the expression levels of NF-L, NF-H, and TuJ1 were significantly increased in npMSCs that had differentiated into neurogenic cells. This result suggests that npMSCs have the potential to differentiate into neuronlike cells.…”
supporting
confidence: 47%
“…Adult stem cells capable of adopting the neural and/or glial phenotypes in vitro can be isolated from murine or human CNS (9)(10)(11), bone marrow (12)(13)(14)(15), umbilical cord blood (16)(17)(18), skin (19), hair follicles (20)(21)(22), adipose tissue (23)(24)(25)(26)(27)(28)(29), or dental pulp (30,31). Stem/progenitor cells isolated from murine and human skeletal muscles by various methods give rise to progeny cells with neuronal and glial phenotypes (12,(32)(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…These cells have also shown increased viability and proliferation when exposed to LILI alone [5] and, as well as, in combination with epidermal growth factor (EGF) [28]. Recent studies have demonstrated the functional neural differentiation of human ADSCs [29]. Adipose stem cell treatments have been used in animals without adverse effects [30] and several clinical trials are underway in humans that have shown no adverse effects to date [31].…”
Section: Adipose Derived Stem Cellsmentioning
confidence: 99%
“…By 2007, in France, 32% of the deaths were caused by cardiovascular disease [2]. Since stem cells have the ability to self renew and differentiate into multiple lineages [3], these cells could be used in cellbased therapy for repairing and regenerating various tissues and organs. Many studies have been done involving LILI and stem cells, both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%